Group Counseling with Assertive Training Techniques to Self Confidence Adolescents - Dewantari, Tri; Surya, Barep Hapit; Bulantika, Siti Zahra (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This research aims to see the increase in students’ self-confidence by using group services with assertive training techniques. The method used in this study was a quasi-experimental method with a non-equivalent control group design. The sample in this study were twelve students, aged 13-14 years at SMP Muhammadiyah 3 Depok Yogyakarta. The instrument used in this study was a self-confidence scale. Analysis of the data used Wilcoxon test analysis and Mann-Whitney test. The results of the study showed that group guidance services with assertive training techniques had an effective effect on increasing student self-confidence. This can be seen from the increased self-confidence of students in the experimental group which has increased compared to the control group who was not treated with Assertive training techniques.